Bloodstream infections - Rogowska-Borettini, Kinga; Malmur, Paweł Arkadiusz; Biaduń-Mućko, Weronika; Romanowska, Aleksandra; Wysieńska, Maria; Jóźwiak, Piotr; Rybak, Adam (Quality in Sport, 2026)
Vascular bed infections (BSI) are a significant clinical problem. They are characterized by a high mortality rate, which is both a diagnostic and therapeutic challenge. The aim of the study is to discuss in detail the etiology, epidemiology and classification of bloodstream infections, as well as their impact on inpatients and outpatients. Vascular bed infections can be classified as nosocomial or community-derived, and the incidence varies depending on the age group and the patient’s contact with the medical community. In particular, older patients and immunocompromised patients are at higher risk of developing BSI, which is associated with a higher risk of severe complications such as sepsis and septic shock. Blood cultures are primarily used in diagnostics, but new technologies such as MALDI-TOF can speed up the process. Treatment is based on early initiation of antibiotic therapy, which should be adapted to the sensitivity of the pathogens and the source of infection. The paper also highlights the importance of monitoring bacterial resistance and adapting therapies to the changing epidemiological profile. The conclusions of the study are aimed at increasing the effectiveness of diagnosis and treatment of vascular bed infections, which is crucial in improving patients’ health outcomes.